MARINE EDUCATION IN INTERNATIONAL INDUSTRY - Ivan I. Kostylev; Mikhail K. Ovsyannikov (Moscow Polytechnic University, 2016)
The article deals with the maritime education as industry!based staff training. Within the framework of Russian higher education system, industry!based education should not be considered as secondary or peripheral. Training of personnel for shipping industry is carried out on the basis of the national standards and in compliance with the requirements of the International Marine Organization, which is a part of the United Nations Organization. Integration of the maritime education into the world practice had started long before the Bologna system implementation, which is viewed sometimes as an access to European standards. Training of personnel for shipping industry in different countries is based on international and national standards. The organizations uniting the international maritime educational community are the World Maritime University in Malmö, Sweden, International Association of Maritime Universities, International Maritime Lecturers Association and regular conferences on shipping safety. Maritime education aims at the implementation of the state obligations inasmuch international conventions are ratified by the Russian government.